Perioperative management for transposition of great arteries - Ajay Kumar Gupta; Vishal K Singh (Wolters Kluwer Medknow Publications, 2014)
Transposition of the great arteries (TGA) is a congenital heait defect 111 which the normal anatomic positions of the aorta and pulmonary artery are transposed (ie. the aorta originates from the right ventricle and the pulmonary artery arises from the left ventricle). The association with other cardiac malformations such as ventricular septal defect and left ventricular outflow tract obstruction is frequent and dictates timing and clinical presentation, which consists of cyanosis with or without congestive heait failure. Newborns with TGA/ intact ventricular septum frequently need preoperative stabilization with PGEr mechanical ventilation and/ or Balloon Atrial Septostomy(BAS). The arterial switch operation is the procedure of choice that restores the aoita and pulmonary artery to their normal anatomicpositions. Intensive support is required to support the left ventricle which faces high resistance systemic circulation postoperatively. The outcome for most of the patients after surgery is good with low incidence of residual defects. Long term follow up is required for concerns regarding neurologic outcome and coronary abnormalities. This review focuses on current standard of care for patients with TGA.